DEIXIS ANALYSIS IN “A NIGHT AT THE OPERA” ALBUM - Vincent Cahya Buana; Wiwiek Sundari (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
This research discussed types of deixis found in Queen’s album entitled “A Night At The Opera”. It is aimed at revealing the deixis in the song lyrics and explaining the deictic words used by all members of Queen by utilizing the theory of deixis as the analysing tool. The deixis was collected from 11 (eleven) songs’ lyrics on the album by using observation and audio-visual material techniques. The lyrics were copied into.docx format so that the researchers can matched the lyrics while listening to the songs before finally analyse the deixis in it. The result shows that this album contains the whole types of the deixis listed in Levinson’s theory of deixis. The most dominant deixis wasperson and time deixis, while the least dominant one is discourse. The result also exposes the mostly used type of deixis by all members of Queen, that is, first person deictic words since the whole 11 songs in the album mostly told their fans or song listeners about their own story or experience.Keywords: deixis, reference, context, song lyrics